HUBUNGAN BEBAN KERJA DENGAN KEJADIAN COVID-19 PADA DOKTER DAN PERAWAT DI RUMAH SAKIT DARURAT COVID (RSDC) WISMA ATLET - Chrisshanti Putri Pasaribu, (2021)
DKI Jakarta is one of the provinces with the most COVID-19 cases in Indonesia. Health workers both globally and nationally are infected and death from COVID19. DKI Jakarta ranks third with the highest number of doctors who died. The purpose of this study was to find out the relationship between workload and COVID-19 events in doctors and nurses at RSDC Wisma Atlet. This research is a quantitative analytical research with case control method. The samples in this study amounted to 64 respondents with 32 cases and 32 controls taken with purposive sampling techniques. Independent variable in this study is workload, dependent variable is COVID-19, and confounding variables are gender, job type, age, and placement field. The questionnaire used in this study used a standard NASA-TLX questionnaire to measure the workload and epidemiological investigation form of the Ministry of Health to measure the incidence of COVID-19. Bivariate analysis using chi square test and multivariate analysis using multiple logistic regression test with α=0.05. The results in this study show that workload has a relationship with COVID-19 events (p=0.045, OR=3,215). Gender variables (p=1,000, OR=1,000), job types (p=0.787, OR=0.747), age (p=0,708, OR=0,5), and placement fields (0.258, OR=2,270) that indicate that there is no association with COVID-19 events. Variables Based on multivariate analysis found that workload variables have a relationship with COVID-19 events after controlling for confounding. Advice for RSDC Wisma Atlet, this research can be the basis for re-regulation of existing health resource management and for respondents is expected to maintain a good lifestyle and always adhere to existing handling regulations.